2023
DOI: 10.1021/acs.energyfuels.3c02399
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Utilization for Hydraulic Fracturing of Shale Reservoir, and Geo-Storage: A Review

Nikita Gupta,
Amit Verma

Abstract: Hydraulic fracturing has completely revolutionized how shale resources are exploited to extracthydrocarbons. However, sustainability and environmental issues have fueled the desire for alternate fracturing technologies. Supercritical carbon dioxide (Sc-CO2) fracturing is a new method that uses high-pressure, high-temperature CO2 in its supercritical state (7.38 MPa and 31.1 °C) to generate fractures in shale formations, thereby increasing reservoir permeability. This Review thoroughly analyzes the effects of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 167 publications
0
2
0
Order By: Relevance
“…CO 2 fracturing can avoid water sensitivity and water block effects, as it replaces waterbased fracturing fluids with CO 2 [25][26][27]. Therefore, it has been widely applied in shale reservoir development in recent years [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 fracturing can avoid water sensitivity and water block effects, as it replaces waterbased fracturing fluids with CO 2 [25][26][27]. Therefore, it has been widely applied in shale reservoir development in recent years [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of SC-CO 2 as an alternative to water for enhanced shale oil and gas extraction has become the frontier of research in recent years . Some scholars have shown that the utilization of SC-CO 2 for reservoir fracturing modification can aid in shale oil and gas extraction. , Injecting CO 2 into oil reservoirs can enhance oil recovery and effectively sequester CO 2 . This technique has been proven to be the most economically valuable carbon capture, utilization, and storage (CCUS) technology. , This approach achieves the goals of sequestering carbon dioxide and enhancing the recovery rate of shale oil and gas reservoir rocks.…”
Section: Introductionmentioning
confidence: 99%